Pelabelan -k total tak reguler sisi para graf tas dan graf pura - Sauki; Meryta Febrilian Fatimah -; Eka Putri Ayu Lestari (Journal of Mathematics: Theory and Applications, 2020)
Given that G is a simple and connected graph with a set of points and sides, that is, denoted and respectively. The labeling –k total of irregular edges of graph G is that each edge has a different weight. The smallest k value contained in the labeling -k total irregular edges is called the irregular strength of the total side of G which is denoted by the test (G). In this paper, the author examines the irregular strength of the total side of the bag graph and the temple graph. The bag graph is denoted by Ts (n) with the test value and the temple graph is denoted by Pu (n) with the test value